Influência de malhas fotoconversoras e diferentes substratos na produção de mudas de Annona squamosa L. - Sakasaki, Roberto Tadashi (2015)
The culture of Annona squamosa L. stands out among the medium sized annonaceae as one of the most cultivated around the world, distributed in various countries. The species has aroused interest from producers and researchers in the Northern Region of the Amazon, by the growing demand of its consumption, and converted this fruitful in a related priority to the development of seedling production technologies and management to assure the formation of uniform orchards and fruit production quality. However, this specie is consider promissory and lacks scientific and technical information on its management in the region. Thus, the objective of this study to evaluate the effects of differant shading nests and substrates in the production of Annona squamosa L. in Cerrado conditions in Boa Vista RR. The experiment was conducted in a completely readomized disegn in factorial 4x4. We used four screen house environments covered with photon convertor meshes (silver and red with 35 and 50%) and four compositions of substrates made from the mixture of organic compounds (chicken manures, cattle and sheep). The arithmetic mean submitted to F-test and compared by Tukey test at 5% probability. A larger development of seedlings of sugar apple are obtained with the substrates consisting of soil, sand and muck of chicken and/or beef associated with the silver-colored ChromatiNet photon convertors mesh Silver 35 and 50% and 35% Red.